2018
DOI: 10.1111/jam.14116
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactisKR-050L extract suppresses house dust mite induced-atopic skin inflammation through inhibition of keratinocyte and mast cell activation

Abstract: Aims: Atopic dermatitis (AD) is a chronic inflammatory skin disease, with a steadily increasing prevalence. Lactic acid bacteria (LAB) have been widely used in the food industry and are an attractive option for preventing and treating allergic skin diseases. We previously isolated new LABs including Lactococcus lactis KR-050L from Gajuknamu kimchi, and showed the anti-inflammatory effects of extract of L. lactis KR-050L culture broth (LLK). In this study, we investigated the effects of LLK on AD. Methods and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In vitro studies have also shown that Lactococcus lactis KR-050L suppresses pro-inflammatory cytokines and chemokines in keratinocytes by suppressing gene expression responsible for pro-inflammatory cytokine and chemokine production. 29 To our knowledge, our study is the first in vivo study in humans investigatingLactococci in the treatment of AD.…”
Section: Discussionmentioning
confidence: 91%
“…In vitro studies have also shown that Lactococcus lactis KR-050L suppresses pro-inflammatory cytokines and chemokines in keratinocytes by suppressing gene expression responsible for pro-inflammatory cytokine and chemokine production. 29 To our knowledge, our study is the first in vivo study in humans investigatingLactococci in the treatment of AD.…”
Section: Discussionmentioning
confidence: 91%
“…NF-κB plays critical roles in development, survival, oxidative stress, inflammation and activation of B lymphocytes (Herder et al, 2015; D’Addio and Fiorina, 2016; Sasaki and Iwai, 2016; Jin et al, 2018). NF-κB was identified as one of the key regulators in the immunological setting.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In particular, it has excellent control effects against allergic diseases including allergic rhinitis, allergic asthma, food allergy, and AD. [17][18][19] Probiotics control immune responses via various mechanisms. They can regulate maturation through contact with DCs and influence their interaction with other immune cells to polarize antigenspecific T cell responses to Th1, Th2, Th17, or regulatory T (Treg) cells.…”
Section: Introductionmentioning
confidence: 99%